2021
DOI: 10.3389/fphar.2021.780790
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Review: GSDME-Mediated Pyroptosis in Diabetic Nephropathy

Abstract: Pyroptosis is a recently identified type of lytic programmed cell death, in which pores form in the plasma membrane, and cells swell, rupture, and then release their contents, including inflammatory cytokines. Molecular studies indicated that pyroptosis may occur via a gasdermin D (GSDMD) and caspase-1 (Casp1) -dependent classical pathway, a GSDMD and Casp11/4/5-dependent non-classical pathway, or a gasdermin E (GSDME) and Casp3-dependent pathway. Studies of animal models and humans indicated that pyroptosis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 164 publications
(245 reference statements)
1
22
0
Order By: Relevance
“…Gsdme deficiency decreases disease incidence and severity in a collagen-induced arthritis mouse model (79). Interestingly, the same caspase3-dependent GSDME-mediated pyroptotic pathway is seemingly involved in type 1 diabetes progression and diabetic nephropathy, a severe co-morbidity of diabetes (15). Future studies should reveal whether this route towards pyroptosis is more broadly activated in such conditions.…”
Section: Dysregulated Gsdm Activation In Non-infectious Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…Gsdme deficiency decreases disease incidence and severity in a collagen-induced arthritis mouse model (79). Interestingly, the same caspase3-dependent GSDME-mediated pyroptotic pathway is seemingly involved in type 1 diabetes progression and diabetic nephropathy, a severe co-morbidity of diabetes (15). Future studies should reveal whether this route towards pyroptosis is more broadly activated in such conditions.…”
Section: Dysregulated Gsdm Activation In Non-infectious Diseasesmentioning
confidence: 97%
“…When administered to mouse CAPS models, this drug blocked IL-1b maturation and pyroptosis and prevented the autoinflammatory spectrum disorder associated with inflammasome hyperactivation in these mice (90). Possibilities for targeting the caspase-3/ GSDME axis are on the horizon, with a recent pre-clinical study reporting the successful use of Z-DEVD-FMK to ameliorate tubulointerstitial fibrosis and declining renal function in diabetic mice (15). In summary, the idea of targeting GSDMs for the treatment of inflammatory disorders is in its infancy, but these studies represent a promising indication of future potential.…”
Section: Therapeutic Targeting Of Gsdmsmentioning
confidence: 99%
“…It was suggested that activation of GSDME plays a potentially critical role in DKD ( Wen et al, 2020 ). A mini-review convincingly suggested that GSDME-mediated pyroptosis is a critical contributor to the pathogenesis and progression of DKD ( Li W. et al, 2021 ). Furthermore, an elevated expression of GSDME-N was observed in a chronic kidney disease model.…”
Section: The Role Of Gsdme In Diseasesmentioning
confidence: 99%
“…It is a form of lytic programmed cell death initiated by inflammasomes, and HMGB1 released from pyroptotic renal tubular cells amplified inflammatory responses, which recruits immune cells to promote tissue healing and contributes to renal fibrogenesis ( Raupach et al, 2006 ; Li Y. et al, 2021 ). GSDME-mediated pyroptosis is responsible for renal tubule injury and subsequentially fibrosis induced by ureteral obstruction, 5/6 nephrectomy, and DN ( Li W. et al, 2021 ; Li Y. et al, 2021 ; Wu et al, 2021 ). For more details, interested readers may refer to these excellent recently published reviews.…”
Section: Other Programmed Cell Death and Ferroptosis In Renal Fibrosismentioning
confidence: 99%